1997
DOI: 10.1051/aas:1997377
|View full text |Cite
|
Sign up to set email alerts
|

Obscured AGB stars in the Magellanic Clouds

Abstract: Abstract. We have selected 198 IRAS sources in the Large Magellanic Cloud, and 11 in the Small Magellanic Cloud, which are the best candidates to be mass-loosing AGB stars (or possibly post-AGB stars). We used the catalogues of Schwering & Israel (1990) and Reid et al. (1990). They are based on the IRAS pointed observations and have lower detection limits than the Point Source Catalogue. We also made cross-identifications between IRAS sources and optical catalogues.Our resulting catalogue is divided in 7 table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 21 publications
(46 reference statements)
6
68
0
1
Order By: Relevance
“…We complement our sample with objects from van Loon et al (1998) and Trams et al (1999) A further 34 IRAS-detected objects with spectral subclassification are available from Loup et al (1997;their …”
Section: Additional Samplesmentioning
confidence: 99%
“…We complement our sample with objects from van Loon et al (1998) and Trams et al (1999) A further 34 IRAS-detected objects with spectral subclassification are available from Loup et al (1997;their …”
Section: Additional Samplesmentioning
confidence: 99%
“…The targets were selected from IRAS sources (Loup et al 1997;Groenewegen & Blommaert 1998), sources observed with ISO (Groenewegen et al 2000;Cioni et al 2003), and Spitzer IRS targets (Kraemer et al 2005Sloan et al 2006;Lagadec et al 2007;Sloan et al 2008). These include six stars in the intermediate-age populous star cluster NGC 419, of which the four bluest and least dusty stars would probably not have been selected had they not been part of the cluster sample of Spitzer targets.…”
Section: Target Selectionmentioning
confidence: 99%
“…Searches for LPV's seem to be reasonably complete for optical Miras, but were not sensitive enough to extract semi-regular and irregular variables. For TP-AGB stars with high massloss rates, only the brightest and most luminous ones could have been detected by IRAS (Loup et al 1997), missing obscured AGB stars with luminosities lower than about 10 4 £0. Finally, AGB stars with intermediate mass-loss rates, well known and numerous in our Galaxy, would have been completely missed both by optical/I-band and IRAS searches.…”
Section: Brief History Of Previous Surveysmentioning
confidence: 99%